STUDI LITERATUR TENTANG SELF-EFFICACY AKADEMIK REMAJA - Devi Dwi Kurnia; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Self-efficacy is the belief that a person has in his ability to do something sothat he can overcome obstacles or obstacles in achieving the expected goals. This study aimsto determine how adolescents' academic self-efficacy is, to find out whether there are factorsthat influence self-efficacy, to find out whether there are efforts to increase academic selfefficacyin adolescents. This research is a literature study research. The instrument used inthis research is a combination of national and international journals. Data analysis in thisstudy used qualitative. The results show that the phenomenon that occurs in students'problems is based on several triggers for low self-efficacy, including understanding failure,seeing others fail, being influenced by other people and physical conditions that formirrational thoughts that are not necessarily true so that students are unable to solve things.regarding the desired goal.Key Words: Literature study, Self-Efficacy, Adolescents